TRI DHARMA AS A CATALYST FOR MORAL LITERACY AND ETHICAL MINDSET: A REVIEW OF CONTEMPORARY INDONESIAN EDUCATIONAL AND CULTURAL DISCOURSES - Chow Teng Poh; Ni Nyoman Parwati; Ketut Agustini; I Made Tegeh (QANUN: Journal of Islamic Laws and Studies, 2025)
This review synthesizes current literature on Tri Dharma Perguruan Tinggi (the Indonesian higher education) philosophy that encompasses education, research, and community service, as a foundational ethical framework to promote moral literacy and an ethical mindset among learners and citizens. Rooted in the nation’s post-independence vision, Tri Dharma is not merely an academic mandate but a holistic moral philosophy that informs intellectual development, civic responsibility, and community well-being. By drawing on policy documents, ethnographic fieldwork, empirical educational studies, and national reform initiatives, this paper examines the ways in which Tri Dharma has been operationalized across diverse institutional and community contexts. The findings reveal that Tri Dharma fosters a values-driven education model that integrates compassion, critical thinking, and social justice into both formal instruction and public engagement. It bridges traditional Indonesian virtues, such as gotong-royong (mutual cooperation), bhineka tunggal ika (unity in diversity), and cinta tanah air (love for the homeland), with contemporary societal challenges like environmental degradation, digital ethics, and national fragmentation. By highlighting transformative programs such as Gerakan Literasi Nasional, Kartu Prakerja, and ecological initiatives grounded in local wisdom, this review underscores the ongoing relevance of Tri Dharma in cultivating ethical, reflective, and civically engaged citizens in an increasingly globalized and complex world.